2010
DOI: 10.1071/fpv37n4_fo
|View full text |Cite
|
Sign up to set email alerts
|

Foreword: Understanding how plants cope with acid soils

Abstract: Abstract. Supplying food and fuel to meet the demands of a growing population is a challenge facing every society. Crop yields will need to increase significantly over the next 40 years to support an extra two billion people by 2050. Acid soils limit plant production around the world but especially in the tropical and sub-tropical latitudes where a large proportion of the population increases are expected to occur. Aluminium toxicity and phosphorus deficiency are two of the major stresses affecting plant growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The quest should continue for rapid and costeffective analytical methodologies for both laboratory and field situations. Analytical technologies have recently emerged that extend the nature of data generated beyond that provided by conventional dry combustion analyses including: laser-induced spectroscopy (Herrmann et al 2005;Bai and Houlton 2009), inelastic neutron scattering (Rawluk et al 2001;Li et al 2005), and near-and mid-infrared spectroscopies (Gerber et al 2010;Ma and Ryan 2010). Research should be directed towards the possible extension of these technologies to field-based approaches capable of accounting for spatial variability.…”
Section: Modelled Valuesmentioning
confidence: 99%
“…The quest should continue for rapid and costeffective analytical methodologies for both laboratory and field situations. Analytical technologies have recently emerged that extend the nature of data generated beyond that provided by conventional dry combustion analyses including: laser-induced spectroscopy (Herrmann et al 2005;Bai and Houlton 2009), inelastic neutron scattering (Rawluk et al 2001;Li et al 2005), and near-and mid-infrared spectroscopies (Gerber et al 2010;Ma and Ryan 2010). Research should be directed towards the possible extension of these technologies to field-based approaches capable of accounting for spatial variability.…”
Section: Modelled Valuesmentioning
confidence: 99%
“…Furthermore, some studies have shown that P deficiency is another important factor that restricts plant growth, particularly in the tropical and subtropical regions, which are characterized by highly weathered acidic soils. Acidic soil contains many chemical compounds, such as ferric oxide and alumina, that fix P in forms that are unavailable to plants [ 21 ]. The P use efficiency is very low under Al stress, particularly in acid soils with high levels of toxic Al, because Al-P compounds are insoluble [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum toxicity and P deficiency are two main constraints for crop growth in acidic soils (Kochian et al, 2004;Ma and Ryan, 2010;Zheng, 2010). Aluminum toxicity and P deficiency are two main constraints for crop growth in acidic soils (Kochian et al, 2004;Ma and Ryan, 2010;Zheng, 2010).…”
Section: The Aluminum-phosphorus Interactionmentioning
confidence: 99%